Job Satisfaction and Migration Intention of Health Information Managers in Nigerian Health Sector (Lead City International Journal of Library, Information & Communication Sciences, 2024)
A large-scale migration of health practitioners was observed. Therefore, the study in bid to understand factors that causes this migration aimed at understanding the influence of job satisfaction on migration of health information managers in Nigeria. The survey research design was adopted; the population of the study consist of eighty (80) health information management professionals in the Lagos hospitals. Total enumeration was used for the study which make do for the sampling of all the eighty (80) health information managers. A structured questionnaire was adapted to gather data for the study. Descriptive and inferential statistics were used for analysis. The study found a moderately high-level migration intention among health information management practitioners with financial, cultural and environmental consideration service as the push and pull factors for the health practitioners. The test of hypothesis revealed that Job satisfaction ((R = 0.955, p<0.05) have significant influence on migration intention of health information managers. The study concludes that emigration intention among health information manager is on the increase and it is mainly due to lack of job satisfaction. It is therefore recommended that hospital management in Nigeria pay attention to motivators and hygiene factors capable of contributing to the job satisfaction of health information management practitioners.